Dynamical Properties of a Bose Gas with δ-like Interaction between Particles at Temperatures above the Phase Transition Point and in the Limit of Strong Interparticle Repulsion - Pastukhov, V.S. (Ukrainian Journal of Physics, 2022)
Exact equations for the one-particle Green's function and for the irreducible part of the two-particle Green's function of a three-dimensional Bose gas with point-like interaction between particles have been derived in the framework of the functional integral approach. The two-particle spectrum of the system has been analyzed in detail in the simplest approximation, which makes allowance for all two-particle scattering processes. The leading asymptotics of the single-particle spectrum in the long-wave range was shown to remain quadratic. The critical temperature was found in the limit of strong repulsion between particles.